Non-Pharmacological Strategies to Reduce Bloating and Abdominal Distension: A Systematic Review - Fedi Sudrajat; Suyanto Suyanto; Erna Melastuti; Dwi Retno Sulistyaningsih (GLOBAL HEALTH SCIENCE GROUP, 2025)
Bloating and abdominal distension are common complaints that can be caused by various factors, including intestinal motility disorders, postoperative effects, and functional digestive disorders. While pharmacological therapy is often used, various non-pharmacological interventions have been developed as safer alternatives with minimal side effects.This literature review aims to examine various non-pharmacological interventions for addressing intestinal motility disorders, bloating, and abdominal distension based on available evidence. A search for scientific articles, including randomized clinical trials and randomized controlled trials, was conducted using inclusion and exclusion criteria based on the PICOS format. Articles were retrieved from databases such as Google Scholar, PubMed, ScienceDirect, and CINAHL (2018–2025), focusing on publications in English and Indonesian. Keywords related to bloating, flatulence, and abdominal distension interventions were used to identify relevant studies. The process of searching for high-quality research articles was conducted using the PRISMA 2020 diagram. Initially, 831 articles were identified, with 648 eliminated due to duplication, being outside the topic, or lacking full-text access. This resulted in 183 articles screened. After the eligibility assessment, 170 articles were further excluded for not meeting the inclusion and exclusion criteria. The final selection process resulted in 13 articles that were included and discussed in this study. Non-pharmacological interventions have been shown to effectively reduce bloating and accelerate the recovery of intestinal peristalsis. Specific interventions include: (chewing gum, which promotes flatus release and defecation; mentha spicata L. essential oil, which has analgesic properties and reduces bloating; warm compresses, which significantly enhance intestinal peristalsis; thoracoabdominal biofeedback, which effectively reduces abdominal distension; early mobilization, which accelerates the recovery of intestinal peristalsis and lowers the risk of postoperative ileus; chamomile, which has therapeutic effects in reducing flatulence and distension; coffee or caffeine consumption, which significantly promotes intestinal function recovery. Non-pharmacological interventions have proven effective in alleviating symptoms and accelerating the recovery of intestinal peristalsis, bloating, and abdominal distension.